The revolving door of reform: Professionalism and the future of probation services in England and Wales - Tangen, James (Probation journal, 2018)
Reform of probation services in England and Wales has been a frequent feature of its history, though the pace of review, restructuring and modification has increased exponentially in the last 30 years. This paper provides a brief history of changes to the National Probation Service since its inception in the Criminal Justice and Court Services Act 2000 to the recent announcements of the merger of prison and probation services into a new agency, Her Majesty’s Prison and Probation Service. Commonalities are identified between the various programmes of reform instigated throughout the last 17 years, drawing on insights from Pollitt. The paper addresses the implications for the future of a public probation service in England and Wales after the National Offender Management Service (NOMS) ceased to exist in April 2017 and Her Majesty’s Prison and Probation Service was inaugurated.